Water Resources In Algeria - Abdessalam, Farida; Redjem, Khaled; Baddou, Abdelrrahmane (جامعة الوادي University of Eloued, 2025)
The importance of studying the subject of water resources in Algeria has emerged due to several social and natural factors. These include the significant increase in demand for this valuable and strategic resource for development, as well as the decline in water reserves due to irregular climatic conditions (drought), increased agricultural water usage, and the absence of rational, sustainable, effective, and efficient management. Additionally, the relative rise in population growth has led to increased consumption of drinking water and increased water pollution due to industrial waste and environmental degradation from various economic activities in general. All these factors highlight that the water problem in Algeria manifests differently across regions. Therefore, as a result of these factors, it is necessary to reconsider the water resources management plan by developing an effective and purposeful national water strategy to preserve these resources, ensure their sustainable and efficient use, and meet the requirements of the principle of sustainable development. This should also take into account the economic cost of water and ensure sustainable human development.
Water Resources in Algeria: Factors of the Problem and the Adopted and Possible Solutions
Keywords: Water; Water Strategy; Water Resources